Innate and learned behaviour, habituation of technology and emotions of cattle: Literature review - Kovács, Levente; Kézér, Luca; Tőzsér, János (Animal welfare, Ethology and Housing Systems (AWETH), 2025)
Innate and learned behaviour of cattle are presented in this paper. Habituation to housing and milking technology of dairy cows, learning mechanisms and attitude towards routine husbandry procedures and humans of calves and mature animals are reviewed. Positive and negative emo-tions expressed in the course of social communication and farmers are discussed. Feeding behav-iour, aggression and parent–offspring interactions as well as stereotypes and its development are also pointed out.
Keywords: cattle; behaviour; learning; emotions; stereotypes